STRATEGI MEDIA RELATIONS HUMAS PT,PERKEBUNAN NUSANTARA V PEKANBARU ( PTPN V) PEKANBARU DALAM MENINGKATKAN CITRA POSITIF - Muhammad Arovi; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
PT. Perkebunan Nusantara V is a state-owned company, a company that grows and develops in a society will always face pressure, both of which come from outside the company or from within the company itself. The rapid advancement of information technology applied in the world of mass media and competition in the industry business press, mass media demanded Public Relations of PT. Perkebunan Nusantara V to be able to follow the development is happening especially concerning the issue of the company itself. The field of Public Relations of PT. Perkebunan Nusantara V tasked to perform the functions of public relations through the management and delivery of news or information and cooperation with the mass media in creating positive public opinion. The aim of this study was to determine the Public Relations PT. Perkebunan Nusantara V Pekanbaru in managing relations with the mass media, to find out Public Relations PT. Perkebuan Nusantara V Pekanbaru in developing a strategy with the media and to learn Public Relations PT. Perkebunan Nusantara V Pekanbaru in developing a network with the media.This research uses qualitative descriptive method. Data collection techniques used were based on the fact the field through observations, interviews, and documentation. Informants in this study amounted to 7 people. In conducting the data analysis performed data reduction as sharpening process, classify, direct, dispose of unnecessary, and organize data in a way such that it can be deduced and verified. for checking the validity of the data the researchers used a technique extension of participation and triangulation.The results showed that PT. Perkebunan Nusantara V Pekanbaru in managing relationships do know well how the existing media both print and online, making media such as family, giving an expression of sympathy, understanding each other's needs. In developing the strategy with the media PT. Perkebunan Nusantara V Pekanbaru cooperate in such activities, Advertising in mass media, press releases, press conferences, press tours and press gathering, event (activities). Such activities undertaken to achieve as much positive publicity.